Land Rights and Legislation: Uncovering the Veil of Property Law in Indonesia - Basri (Ilomata International Journal of Social Science, 2024)
This study examines the complex terrain of property rights in Indonesia, revealing gaps, historical trends, legislative impact, and theoretical insights. The method used is qualitative. Legal writings (constitutions, statutes, commentaries), court decisions, policy papers, and historical records relating to property and land rights law in Indonesia were considered as the primary research sources. Data were analysed using triangulation and N-Vivo. The results show that modern property law is the result of historical developments characterised by post-independence changes and colonial legacies. A careful balance is required to address the challenges posed by the encroachment of economic interests on legislative provisions intended to protect people's rights. The results show that modern property law is the result of historical developments characterized by post-independence changes and colonial legacies. A careful balance is required to address the challenges posed by the encroachment of economic interests on legislative provisions intended to protect people's rights. The weaknesses and contradictions found in the legislative framework highlight the need for flexible solutions to meet the changing demands of society. The intersection between Islamic law, state law and customary law is best understood through the lens of legal pluralism theory. The consequences for marginalized groups highlight the urgency to prioritize their rights, which requires community engagement and participatory legal reform. The theoretical implications of legal pluralism support it as an analytical instrument, and the comparative analysis places Indonesia in a global context and offers suggestions for useful policy responses. The study concludes by recommending a flexible legal framework, international cooperation, and further investigation to support a more inclusive and egalitarian understanding of land rights in Indonesia.